Characteristics of imbibition in tight oil reservoirs from the perspective of physical experiments and theory. Issue 10 (3rd June 2020) - Cao, Renyi; Wu, Zhiyu; Liang, Xiaowei; Cheng, Linsong; Xu, Zhongyi; Guan, Yun; Guo, Zhuoliang; Jia, Zhihao
Abstract: Imbibition is an important recovery mechanism for tight oil reservoirs, which occurs during hydraulic fracturing and development. Due to the massive distribution of micro‐nano scale pore throats and the existence of a boundary layer in tight formation, agreement consensus has not been reached on the imbibition mechanism. Based on the effect of the boundary layer, experiments were conducted to study the imbibition in tight sandstone, and NMR was used to determine the efficiency of imbibition. The results reveal that the imbibition rate is related to the connection area of the matrix‐fracture, throat connection, and radius. Then, the effective capillary pressure was modified by describing the thickness of the boundary layer in the micro‐nano pore throats. The calculation results show that the existence of boundary layer in micro‐nano throats makes the capillary pressure much larger than those of reservoirs without boundary layer. And the boundary layer reduces the effective flow radius, which dramatically decreases the imbibition quantity. The final result of existence of a boundary layer dramatically weakens the imbibition ability of a tight oil reservoir, and thus, the existence of a boundary layer cannot be ignored. Finally, the effective throat radius limit was analyzed during imbibition in a water‐oil‐rock system of a tight oil reservoir. Without a boundary layer, the effective radius of the pore throats in the water‐oil‐rock system during imbibition is greater than 200 nm, which is due to the advantages of the large capillary force and pore throats that are not too small. With a boundary layer, the main radius of the pore throats used for the water‐oil‐rock imbibition is approximately 400 nm. Thus, the imbibition occurs in the pore throats larger than 200 nm in the water‐oil‐rock system, and a surfactant could reduce the limit of the throat radius during imbibition in tight oil reservoirs. Abstract : Several experiments were carried out to study the imbibition of tight oil sandstone, and NMR was applied to find out the efficiency of pore during imbibing. The effective capillary pressure was modified by accurately describing the characteristic of the thickness of boundary layer in micro‐nano scaled throats. Analysis of and comparison between tight oil reservoir and conventional low permeability reservoir have been made, and calculation results show that the abundant micro‐nano scale throats and existence of boundary layer make capillary pressure much larger than those without the boundary layer.